Case report: An overlooked complication of the dural suture after craniotomy: pseudoaneurysm of the middle meningeal artery with endovascular resolution - Xu, Yao; Li, Xiangdong (Frontiers in Neurology, 2023)
Aneurysms of the middle meningeal artery (MMA) are exceedingly uncommon and mainly result from traumatic brain damage, but this report describes a case of MMA aneurysm induced by cranial surgery. Surgery was performed on a 34-year-old male with cerebrovascular malformation and cerebral haemorrhage. Cerebral angiography revealed no MMA aneurysm before craniocerebral surgery; however, a postoperative angiogram revealed a new MMA aneurysm. Aneurysms of the MMA are uncommon consequences of brain surgery. Based on our findings, the MMA as well as other meningeal arteries should be avoided while suturing the dura mater tent to prevent aneurysms.